2001
DOI: 10.1007/s002770100359
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blood-borne viral infections (cytomegalovirus, human herpesvirus-6, human herpesvirus-7, human herpesvirus-8, human T-cell lymphotropic virus-I/II, human retrovirus-5) among blood donors in Latvia

Abstract: The identification of blood-borne viral infections is important in transfusion medicine. The aim of this study was to evaluate the prevalence of human herpesvirus (HHV) [cytomegalovirus (CMV), HHV-6, HHV-7 HHV-8] and human retrovirus (HRV) (human T-cell lymphotropic virus (HTLV)-I/II, HRV-5) infections among apparently healthy Latvian blood donors. DNA extracted from peripheral blood leukocytes (PBL) of 150 individuals was tested for herpesviruses by sensitive polymerase chain reaction (PCR) technique. None of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…It is also possible that individuals infected with colobus CMV may have remained unidentified because the virus was not shed in saliva and feces or because the applied PCRs did not possess maximum sensitivity for detection of CMVs. Despite this, the 2.6 % HCMV prevalence determined here in a collection of oral and fecal swabs is well in accord with previous PCR-based studies on healthy subjects reporting HCMV detection rates in blood of 0–8 % of children and adults from Uganda, Germany, Latvia, Australia and Japan [ 39 43 ] (studies based on fecal samples were to our knowledge not reported). In addition, sequences of other viruses have been detected previously in the present sample set [ 33 ] indicating absence of PCR inhibitors, and the use of colobus-specific PCR able to identify colobus CMV in control colobus monkey samples indicates this PCR is of sufficient sensitivity to detect colobus CMV present at levels found within its natural host.…”
Section: Resultssupporting
confidence: 91%
“…It is also possible that individuals infected with colobus CMV may have remained unidentified because the virus was not shed in saliva and feces or because the applied PCRs did not possess maximum sensitivity for detection of CMVs. Despite this, the 2.6 % HCMV prevalence determined here in a collection of oral and fecal swabs is well in accord with previous PCR-based studies on healthy subjects reporting HCMV detection rates in blood of 0–8 % of children and adults from Uganda, Germany, Latvia, Australia and Japan [ 39 43 ] (studies based on fecal samples were to our knowledge not reported). In addition, sequences of other viruses have been detected previously in the present sample set [ 33 ] indicating absence of PCR inhibitors, and the use of colobus-specific PCR able to identify colobus CMV in control colobus monkey samples indicates this PCR is of sufficient sensitivity to detect colobus CMV present at levels found within its natural host.…”
Section: Resultssupporting
confidence: 91%
“…The active single HHV-7 and B19 infection, but not active single HHV-6 or active concurrent infection, has been previously detected in Latvian blood donors [33]. The active HHV-6 infection was confirmed by the detection of viral sequence in plasma DNA samples and a concomitant increase of HHV-6 load in PBLs.…”
Section: Discussionmentioning
confidence: 63%